Kinerja Pegawai Berdasarkan Aspek Kepemimpinan Transformasional, Budaya Organisasi, dan Inovasi (Studi Kasus Dinas Syariat Islam Kabupaten Bireuen) - Samsurizal Samsurizal; Evi Arief Syarifuddin; Laina Fadhilah; M. F. Chadafi (Aceh Cooperative Care, 2026)
Employee performance is suspected to be directly and indirectly related to several factors, including transformational leadership, organizational culture, and employee innovation. This research was conducted using a case study of employees at the Bireuen Regency Sharia Office. This study applied a quantitative associative method and used path model statistics to analyze the data. The results showed that: (1) employee performance is directly and indirectly influenced by the causality of transformational leadership (37.52%), organizational culture variables (31.36%), and employee innovation (34.3%). (2) transformational leadership, Organizational culture, and innovation factors collectively impact employee performance by 60,3%. (3) There is a causal relationship between the variables of, transformational leadership, organizational culture, and innovation, with a fairly strong categorization